Analysis of the risk of oncological adverse events associated with infliximab in combination with azathioprine compared to monotherapy: insights from the FAERS database - Qiao, Qian; Sun, Jiachen; Zheng, Ya; Mi, Yingying; Gong, Yanan; Liu, Jiahui; Rui, Wenyue; Ma, Yumei; Zhou, Yongning; Liu, Min (Frontiers in Pharmacology, 2025)
ObjectiveThis study aimed to evaluate the risk of tumor formation with infliximab or azathioprine monotherapy versus their combination, using the FDA Adverse Event Reporting System (FAERS) database.MethodsData were extracted from the FAERS database for patients treated with infliximab, azathioprine, and combination therapy from Q1 2004 to Q2 2024. Signal mining employed methods such as Reported Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Multiple Gamma-Poisson Scaling Assessment (MGPSA) and Bayesian Confidence Interval Progressive Neural Network (BCPNN).ResultsOur analysis of the FAERS database revealed that the highest number of reported cases involved skin-related tumors, both individually and in combination. In terms of sex, the risk of cancer was higher in men compared to women in the infliximab-only and combination groups; however, no sex difference was observed in the azathioprine-only group. Regarding age, we noted an increasing incidence of adverse tumor events in middle-aged and elderly individuals compared to minors, except in the azathioprine group, where age was not identified as an independent risk factor. Additionally, body weight was not found to be an independent risk factor in any of the three medication groups. After controlling for age, sex, and body weight, combination therapy did not increase the risk of tumor development compared to the azathioprine group alone. In contrast, for patients using infliximab alone, combination therapy not only did not elevate the risk of tumor development but also appeared to reduce it. The results of the Weber distribution suggest a random failure-type profile for the infliximab and azathioprine-only group, while an early failure-type profile was observed for the combination therapy. Furthermore, we analyzed the median time to onset and cumulative incidence rates, revealing no significant differences in median time to tumor onset or cumulative incidence rates between the combination therapy and the single agent.ConclusionAfter adjusting for age, sex, and body weight, combination therapy did not significantly increase tumor development risk compared to the azathioprine-only group. Additionally, in patients on infliximab monotherapy, combination therapy appeared to reduce the risk of tumor development.